RI 3942 Exploration of the Copper-Sulfur Deposit Khayyam and Stumble-on Properties Prince of Wales Island. Alaska - Earl L. Fosse (The National Institute for Occupational Safety and Health (NIOSH), 1946)
"Preliminary examination of the Khayyam mine indicated that greater reserves of copper might be found by trenching, sampling, detailed geological and topographical mapping, and diamond drilling. The deposit seemed to be a potential source of sulfur, also, for use in the manufacture of paper pulp.Formal examination of the Khayyam mine by the Bureau of Mines was a follow-up of a preliminary examination made by W.S. Wright and the author on October 19-21, 1944. John Reed and W. S. Twanhofel, of the Geological Survey, visited the property during the summer of 1943 and suggested that the prospect be examined further.Preliminary examination of the Stumble-On claim was made July 1-3, 1945, concomitant with the formal examination of the Khayyam mine 11/2 miles to the west.In its program of exploration of mineral deposits, the Bureau of lanes has as its primary objective the more effective utilization of our mineral resources to the end that they make the greatest possible contribution to national security and economy, It is the policy of the Bureau to publish the facts developed by each exploratory project as soon as practicable after its conclusion. The Mining Branch, Lowell B. Moon, chief, conducts pre¬liminary examinations, performs the actual exploratory work, and prepares the final report, The Metallurgical Branch, R. G. Knickerbocker, chief, analyzes samples and performs beneficiation tests. Both these branches arc under the supervision of Dr. R, S. Dean, assistant director.Special acknowledgment is due Robert S. Sanford, acting chief, Alaska Division, Mining Branch, for his help in the preparation of this report and during the project work.The Khayyam property is situated at 550 18’ north latitude and 1320 24’ west longitude on Prince of Wales Island in Southeastern Alaska. (see fig. 1.) The mine adit is 2,350 feet above sea level, near the summit of a mountain ridge, and 2.8 miles in an airline southwest of the head of McKenzie Inlet, a southern branch of Skown Arm. Skowl arm is navigable by ocean-going vessels .to the mouth of McKenzie Inlet, where reefs and rocky islands limit the channel width to 50 yards. Beyond this point the inlet widens to nearly half a mile. Coast and Geodetic Survey chart 8142 indicates from 12 fathoms of water at this narrow neck to more than 30 fathoms throughout the remainder of McKenzie Inlet, The old ore bunker and dock at the head. of the inlet are beyond repair. A new ore bunker and dock would have to be built if a large-scale mining operation were established.The mine can be reached by trail along the western ridge that lies on the west bank of Omar Creek. The trail is approximately 4 miles in length. The grade is rather steep to an elevation of 1,500 feet, but the last 21 miles can be traveled over gentle slopes along the crest of the ridge.Ketchikan is 30 miles by air and 42 miles by water from the head of McKenzie Inlet. Feed, hardware, fuel oil, lumber, and explosives can be purchased at Ketchikan and delivered by boat to McKenzie Inlet. By using an airplane, all small equipment and camp supplies could be using an airplane, all small equipment and camp supplies could be dropped with cargo parachutes near the mine."